The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1530/erc-18-0502
|View full text |Cite
|
Sign up to set email alerts
|

Targeting autophagy in thyroid cancers

Abstract: Thyroid cancer is one of the most common endocrine malignancies. Although the prognosis for the majority of thyroid cancers is relatively good, patients with metastatic, radioiodine-refractory or anaplastic thyroid cancers have an unfavorable outcome. With the gradual understanding of the oncogenic events in thyroid cancers, molecularly targeted therapy using tyrosine kinase inhibitors (TKIs) is greatly changing the therapeutic landscape of radioiodine-refractory differentiated thyroid cancers (RR-DTCs), but i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 154 publications
0
11
0
5
Order By: Relevance
“…Studies have indicated that gain of TERT function modulates the activity of the mammalian target of rapamycin (mTOR) and induces autophagy, which is required for metabolic rewiring, to scavenge the nutrients that are necessary for fueling cancer cell growth in a challenging tumor microenvironment (26,27). Increasing studies have supported the central role of autophagy in the maintenance and development of various kinds of cancers, including thyroid carcinoma (28). Specifically, autophagy plays important roles in regulating the dedifferentiation process of PTCs, although the data are limited (29).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have indicated that gain of TERT function modulates the activity of the mammalian target of rapamycin (mTOR) and induces autophagy, which is required for metabolic rewiring, to scavenge the nutrients that are necessary for fueling cancer cell growth in a challenging tumor microenvironment (26,27). Increasing studies have supported the central role of autophagy in the maintenance and development of various kinds of cancers, including thyroid carcinoma (28). Specifically, autophagy plays important roles in regulating the dedifferentiation process of PTCs, although the data are limited (29).…”
Section: Introductionmentioning
confidence: 99%
“…Однако существование аутофагии, часто сопровождающей процессы развития резистентности, в том числе и к таргетным препаратам, может снижать эффект такого лечения. Такая постановка проблемы подразумевает развитие комплексных подходов в лечении данной категории больных, в том числе использование таргетных препаратов совместно с веществами, модулирующих процесс «самопоедания» [42].…”
Section: роль молекулярно-генетических маркеров в развитии рака щитовunclassified
“…Показано, что инициация аутофагии на ранних стадиях развития опухоли, до формирования у этих клеток инвазивных свойств и способности к метастазированию, приводит к гибели раковых клеток [34]. В дальнейшем, напротив, особенно на фоне противоопухолевого лечения, активная аутофагия сопровождается развитием метастазов, формированием рецидивов заболевания и резистентности опухоли к лечению [42]. Большинство исследователей сходятся во мнении, что стимуляция аутофагии является универсальным защитным механизмом, предотвращающим развитие рака.…”
Section: аутофагия при развитии злокачественных новообразований щитовunclassified
See 1 more Smart Citation
“…SOR exhibits an excellent antitumor effect on various thyroid cancer cell lines, including dedifferentiated subtypes, leading to tumor cell apoptosis and cell cycle arrest (Broecker-Preuss et al, 2015). Nevertheless, drug resistance and serious adverse events, including hand-foot skin reactions, diarrhea, and hypertension, limit the clinical application of SOR (Wei et al, 2019). Studies have shown that patients with DTC have a higher incidence of adverse events to SOR compared to patients with renal and hepatocellular cancer, and about half of the patients need to reduce the dose to control drug toxicity in phase 2 and 3 trials (Jean et al, 2016).…”
Section: Introductionmentioning
confidence: 99%